The possible involvement of D-amino acids or their metabolites in Arabidopsis cysteine proteinase/cystatin-dependent proteolytic pathway - Gholizadeh, A. (Цитология и генетика, 2015)
Cysteine proteinases and their inhibitors ‘cystatins’ play essential roles in plant growth and development. They are involved in various signaling pathways and in the response to wide ranges of biotic and abiotic environmental stresses. To investigate their possible influence from D-amino acids or their metabolism in vivo, Arabidopsis seedlings were allowed to grow under four physico-chemically different D-amino acids including D-aspartate, D-serine, D-alanine and D-phenylalanine containing media. The reverse transcription polymerase chain reaction (RT-PCR) analysis of cysteine proteinase and cystatin gene expressions showed that the addition of D-amino acid to the plant growth media considerably induce the expression of proteinase transcript while decrease the expression level of inhibitor gene in the leaf and root tissues of the test plant in overall. Based on the obtained results the potential impact of D-amino acids or their metabolism on the activity of cysteine proteinase/cystatin-dependent proteolytic apparatus as well as their possible cooperation were predicted and discussed in the plant system.